ACCOUNTING REGULATIONS AND STANDARDS: THE DEVELOPMENT AND BENEFITS OF IFRS IN NIGERIA - Majeed Ajibola IBRAHIM; Adedeji Daniel GBADEBO (International Journal of Social and Educational Innovation)
International Financial Reporting Standards (IFRS) - a set of high-quality standards introduced by the International Accounting Standards Board in 2001 and have since been adopted by many developed countries for their accounting information system. The IFRS were inaugurated due to the global drive to ensure unified accounting reporting procedures across-country boundaries. Many accounting standards have taken the form of IFRS. Several emerging market economies have officially adopted and implemented use of the IFRS to attract an increase in foreign (and mostly, institutional) investments. The widespread adoption of the standards has made the standard to be considered as one of the greatest accounting changes ever. The article reviews accounting regulations, accounting standards and the IFRS, focusing on the development, benefits, and challenges in Nigeria. We attempt to offer answer to two research questions: What are the benefits of the adoption of the IFRS? Are there challenges confronting the use of IFRS in the Nigeria? Amongst other, we established that the uses include: the improvement accounting quality, present a good network impact by encouraging new nations to take it into consideration, attraction of foreign direct investment and bridge communication gap with stakeholders.